U.S. food policy to address diet-related chronic disease - Matthews, Emily D.; Kurnat-Thoma, Emma L. (Frontiers in Public Health, 2024)
Poor diet is the leading cause of mortality in the U.S. due to the direct relationship with diet related chronic diseases, disproportionally affects underserved communities, and exacerbates health disparities. Evidence-based policy solutions are greatly needed to foster an equitable and climate-smart food system that improves health, nutrition and reduces chronic disease healthcare costs. To directly address epidemic levels of U.S. diet-related chronic diseases and nutritional health disparities, we conducted a policy analysis, prioritized policy options and implementation strategies, and issued final recommendations for bipartisan consideration in the 2023-24 Farm Bill Reauthorization. Recommendations include: sugar-sweetened beverage taxation, Supplemental Nutrition Assistance Program (SNAP) fruit and vegetable subsidy expansion, replacement of ultra-processed foods (UPF) with sustainable, diverse, climate-smart agriculture and food purchasing options, and implementing "food is medicine".